Distinctive Convergence Eye Movements in an Acquired Neurosensory Dysfunction - Balaban, Carey D.; Szczupak, Mikhaylo; Kiderman, Alexander; Levin, Bonnie E.; Hoffer, Michael E. (Frontiers in Neurology, 2020)
In late 2016, diplomats in Havana, Cuba began presenting with a unique symptom complex after perceiving a strange noise and/or feeling a pressure field in their domicile. This report is a retrospective, quantitative analysis of video oculography data of pupillary light reflex performance and binocular disparity-driven eye and pupil movements during the acute time period after the reported exposure. Their patterns of response in these 19 individuals are markedly different than those seen in a group of individuals with usual acute mild traumatic brain injury (17 subjects) and from 62 control subjects (21-60 years old) with no injury. Nonlinear least squares regression was used to estimate model parameters from the eye movement and pupil measurements (Balaban et al., 2018). Linear discriminant analysis was then used to identify a classifier for objective discrimination of the groups with >91% accuracy and no confusion between the acute neurosensory findings among these members of the Havana diplomatic community and subjects with acute mild traumatic brain injury. This pattern difference in eye and pupil behavior may be a useful screen to help objectively distinguish blunt trauma from Havana-type effects in the future and to guide affected individuals to appropriate care.